Perancangan strategi pemasaran di UMKM Bakpia Pathok Bu Susi - Hadisantono; Putri, Louisa Adella Regita; Hanandoko, Theodorus B.; Dewa, Parama Kartika (Jurnal Teknik Industri dan Manajemen Rekayasa, 2024)
[Marketing Strategy Design for Bakpia Pathok Bu Susi SME] Bakpia Pathok Bu Susi SME is one of the bakpia pathok producers in Yogyakarta, capable of producing 3000 to 3500 pieces of bakpia per day. During the COVID-19 pandemic, there was a decline in sales that has not yet been resolved. The main problem that will be solved in this research is the decline in product sales since the COVID-19 pandemic, resulting in not meeting the sales target of 20 boxes per day. This research aims to increase daily product sales by 15% through several proposed improvements and selected effective marketing strategies. The method used in this research is combination of Marketing Mix 7P and SWOT Analysis method. Based on the analysis and solution determination, the chosen solution is to promote through instagram and use whatsapp as an online ordering platform. The implementation of the solution is carried out over a period of 30 days by creating promotional content that highlights the product’s distinctive features and uniqueness. The implementation results in a 22% increase in daily product sales.